2018
DOI: 10.1038/s41371-018-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of miR-33a in monocytes from Mexican hypertensive patients in elevated carotid intima-media thickness

Abstract: miR-33a has been described as a key regulator in the initiation and progression of atherosclerosis. However, its role in arterial hypertension (HTA) has not been elucidated. Therefore, the aim of this study was to determine the association between the expression of miR-33a (5p and 3p) and the carotid intima-media thickness (cIMT) in samples of monocytes and serum from hypertensive patients. The miR-33a-5p and miR-33a-3p expression in monocytes and serum from Mexican hypertensive patients were examined by RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Increase in LDL cholesterol is also progressively and significantly associated with a rise in the prevalence of carotid atherosclerosis (CA), even in the absence of other ‘traditional’ risk factors [ 9 ]. One of the potential mediators in this interplay between CA and LDL cholesterol is miR-33a—a microRNA which is up-regulated in CA [ 10 ] and positively correlated with LDL and total cholesterol levels in type 2 diabetes [ 11 ]. In our study we found that both strands of miR-33a (5p/3p) were associated with higher LDL cholesterol levels in CA patients in a univariable linear regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in LDL cholesterol is also progressively and significantly associated with a rise in the prevalence of carotid atherosclerosis (CA), even in the absence of other ‘traditional’ risk factors [ 9 ]. One of the potential mediators in this interplay between CA and LDL cholesterol is miR-33a—a microRNA which is up-regulated in CA [ 10 ] and positively correlated with LDL and total cholesterol levels in type 2 diabetes [ 11 ]. In our study we found that both strands of miR-33a (5p/3p) were associated with higher LDL cholesterol levels in CA patients in a univariable linear regression model.…”
Section: Discussionmentioning
confidence: 99%
“…“Increased Expression of miR‐33a in Monocytes from Mexican Hypertensive Patients in Elevated Carotid Intima‐Media Thickness” 35 …”
Section: Epigenetic Mechanisms Of Csvd and Its Ris...mentioning
confidence: 99%
“… 31 Distinct profiles of miRNAs have achieved good diagnostic performance for essential hypertension, 32 , 33 possibly impacting the risk of CSVD and hinting at a future role of miRNAs as both diagnostic markers and therapeutic targets. 31 Although it is too early to predict whether these investigations will transform clinical care, they may yield more robust biological insights because they have been performed across multiple ancestries, 34 , 35 , 36 unlike early endeavors of genome‐wide association studies that were restricted to individuals of European ancestry.…”
Section: Epigenetic Mechanisms Of Csvd and Its Ris...mentioning
confidence: 99%
“…Therefore, work has focused on the association between blood cell miRNAs and EH occurrence as well as underlying biological mechanisms. Torres-Paz et al showed that the up-regulation of miR-33a-5p expression in monocytes was significantly positively correlated with carotid intima thickness and increased the risk of hypertension in a Mexican population [11]. Additionally, Yin et al reported that the expression of miR-128 in peripheral blood was gradually up-regulated during hypertension progression, which aggravated myocardial injury through inhibiting c-Met [12].…”
Section: Introductionmentioning
confidence: 99%